2021
DOI: 10.2217/bmm-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and Galectin-3 As Biomarkers of Maladaptive Right Ventricular Remodeling In Pulmonary Hypertension

Abstract: Aim: This study assessed the utility of osteopontin (OPN) and galectin-3 (Gal-3) as biomarkers of maladaptive right ventricular remodeling in pulmonary hypertension (PH). Materials & methods: We examined plasma levels of OPN and Gal-3 in patients with PH (n = 62), dilated cardiomyopathy (n = 34), left ventricular hypertrophy (LVH; n = 47), and controls without right ventricle (RV) or LV abnormalities (n = 38). Results: OPN and Gal-3 levels were higher in PH, dilated cardiomyopathy and LVH than in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Osteopontin, which our LC–MS/MS analysis identified at higher levels in CDH, is highly expressed by pulmonary artery smooth muscle cells and adventitial fibroblasts from patients with pulmonary hypertension 30 , 31 and osteopontin levels in serum correlate with pulmonary hypertension severity 32 , 33 , prompting us to select it for further evaluation. The random forest model suggested that osteopontin was the second most influential variable in predicting CDH, although it did not reach statistical significance, which may change with a larger sample size.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Osteopontin, which our LC–MS/MS analysis identified at higher levels in CDH, is highly expressed by pulmonary artery smooth muscle cells and adventitial fibroblasts from patients with pulmonary hypertension 30 , 31 and osteopontin levels in serum correlate with pulmonary hypertension severity 32 , 33 , prompting us to select it for further evaluation. The random forest model suggested that osteopontin was the second most influential variable in predicting CDH, although it did not reach statistical significance, which may change with a larger sample size.…”
Section: Discussionmentioning
confidence: 92%
“…However, there is no prior suggestion of an association with CDH or pulmonary hypertension. Galectin-3 was reported as a biomarker in pulmonary hypertension and associated right ventricular dysfunction and has been shown to stimulate the proliferation of smooth muscle cells in vitro 32 , 37 39 . It was reported to be elevated in amniotic fluid following cytomegalovirus infection 40 , but an association with CDH was not previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are key regulators of fibrogenesis through their interactions with myofibroblasts, wound healing responses, and production of profibrotic factors like galectin-3, osteopontin, and transforming growth factor- beta (TGF-β) ( 71 74 ). We and others have previously shown that CD163+ and CD206+ cardiac macrophage accumulation and monocyte activation correlates with cardiac inflammation and fibrosis with HIV and SIV infection ( 38 , 75 77 ).…”
Section: Conclusion- Discussionmentioning
confidence: 99%
“…Thus, Gal-3 can prematurely identify the onset of right ventricle remodeling in patients with PAH and is positively associated with the right ventricular systolic and diastolic indices [ 85 ]. On the other hand, Gal-3 was not able to differentiate between adaptive and maladaptive RV remodeling in PAH patients within the study of Keranov et al [ 86 ].…”
Section: Gal-3 In Congenital Heart Diseasementioning
confidence: 99%